2019
DOI: 10.3390/microorganisms7060155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pseudomonas in Heterotrophic Nitrification: A Case Study on Shrimp Ponds (Litopenaeus vannamei) in Soc Trang Province

Abstract: Based on a total of 6,295,650 sequences from the V3 and V4 regions (16S ribosomal RNA), the composition of the microorganism communities in the water of three Litopenaeus vannamei (Decapoda, Whiteleg shrimp; Soc Trang, Vietnam) ponds were identified. Pseudomonas (10–20.29%), Methylophilus (13.26–24.28%), and Flavobacterium (2.6–19.29%) were the most abundant genera. The total ammonia (TAN) concentration (p = 0.025) and temperature (p = 0.015) were significantly correlated with the relative abundance of Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Additionally, most Pseudomonas putida strains are utilized as non-pathogenic bacteria [28]. TT321 and TT322 have been shown to utilize inorganic nitrogen sources for growth [14]. In this study, genes involved in ammonia conversion and ammonia formation were revealed.…”
Section: The Core Genomic Repertoire Involved In Ammonia Conversionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, most Pseudomonas putida strains are utilized as non-pathogenic bacteria [28]. TT321 and TT322 have been shown to utilize inorganic nitrogen sources for growth [14]. In this study, genes involved in ammonia conversion and ammonia formation were revealed.…”
Section: The Core Genomic Repertoire Involved In Ammonia Conversionmentioning
confidence: 95%
“…TT321 and TT322 were isolated from shrimp pond water in Soc Trang province, Vietnam [14]. DNA samples of TT321 and TT322 were extracted using AllPrep ® Bacterial DNA/RNA/Protein Kit (Qiagen, Germantown, MD, USA) following the manufacturer's instructions.…”
Section: Dna Extraction Genome Sequencing and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate levels of water quality parameters are essential condition for the survival of all aquatic organisms’ factors in aquaculture, which is one of the crucial problems restricting the healthy development of aquaculture. (Trung Tran et al, 2019). In the current experiment, the soil placed in the culture tank was taken from the surrounding aquaculture farm.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible reason is that other microorganisms contributed to the process. For instance, Pseudomonas veronii, which was the dominant bacterial species, might have a role, as it possesses the AmoA gene encoding for the oxygen monooxygenase [67][68][69], and its function as heterotrophic nitrifier was already observed in natural and engineered ecosystems. However, more studies are required to confirm this hypothesis.…”
Section: Environmental Parameters Biomass Productivity and Nutrientsmentioning
confidence: 99%